DSC studies on states of water in crosslinked poly(methyl methacrylate-co-n-vinyl-2-pyrrolidone) hydrogels - Ahmad, Mansor B.; Huglin, Malcolm B. (Wiley, 1994)
Mixtures of methyl methacrylate (MMA) with N-vinyl-2-pyrrolidone (VP) of various composition in the presence of fixed concentration of ethylene glycol dimethacrylate (EDMA) have been copolymerized to 100% conversion by γ-irradiation. The resultant solid xerogels were swollen in water to yield hydrogels of equilibrium water contents ranging from 15 to 76wt%. The state of water in the poly(MMA-co-VP) hydrogels has been studied by differential scanning calorimetry (DSC) and the percentages of free freezing, freezable bound and nonfreezing water were found to vary with the xerogel composition, i.e. the degree of hydration of the hydrogels. At low equilibrium swelling, most of the water exists as a non-freezing type, whereas at higher equilibrium swelling the majority of water exists as free freezing water. The maximum number of non-freezing water molecules per VP unit in the hydrogel is about 7.5.